Ultrascale computing systems - Carretero, Jesus; Jeannot, Emmanuel; Zomaya, Albert Y. (Professional applications of computing series, 2019)
This book presents important results and methods towards achieving sustainable ultrascale computing systems. The book covers state-of-the-art technologies and methodologies to address the huge computer processing requirements of big data and the Internet of Things.